Endonasal endoscopic cadaveric dissection of sellar-suprasellar region and cavernous sinus - a descriptive and morphometric study - Sheng, Gee Teak (2011)
Endoscopic skull base surgery has evolved in recent years from technological advancement in medical equipment related especially to the field of optical technology. The paradigm shift that occurred with the introduction of the modem rigid rod lens endoscope into the neurosurgical armamentarium saw the exponential expansion of the role of its use in pituitary tumor and endonasal skull base surgery. Due to the distinct differences between microscope and endoscope optic principles, it is important that familiarity with endonasal endoscopic anatomical landmarks be recognized by the young trainee surgeon in neurosurgery. A morphometric study of the relevant anatomy of endonasal approaches to the sellar and parasellar region is crucial to gain understanding of the anatomy of this region.